PENGARUH EDUKASI PERSIAPAN MENYUSUI TERHADAP PENGETAHUAN KADER POSYANDU TENTANG ASI EKSKLUSIF - Kusumaningsih, F.S.; Kamayani, M.O.A.; Nurhaesti, P.O.Y.; Astuti, I.W. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i01.p01, 2024)
This activity aims to increase the knowledge of posyandu cadres in assisting pregnant and breastfeeding mothers to provide exclusive breastfeeding in Peguyangan Kaja Village, North Denpasar. The method used was providing education with lectures and breastfeeding simulations (the first 1000 days of life, the meaning of exclusive breastfeeding, how to breastfeed, problems that often occur during breastfeeding and their solutions, correct breastfeeding practices, and assessing the adequacy of breast milk for babies) to 25 people Posyandu cadres. The results of the Wilcoxon Signed Rank Tests showed a significant change in the knowledge of posyandu cadres before and after being given the intervention (p < 0.005). These results indicate that there is an influence of the education provided on the level of knowledge of posyandu cadres. Education through simple lectures and simulation activities can be used to increase the knowledge and understanding of posyandu cadres in carrying out their duties, such as assisting pregnant and breastfeeding mothers, providing information, motivation and support to provide exclusive breastfeeding, so that babies get the best nutrition for their growth and development. Keywords: exclusive breastfeeding, cadres, education, simulation